The complete chloroplast genome sequence of Begonia arachnoidea (Begoniaceae) - Da-Yan Tao; Hai-Xia Yan; Jin-Ye Zhou; Jian-Bo Rong; Qian Song; Shi-Kai Guan; Shuming Luo (Mitochondrial DNA. Part B. Resources, 2022)
There are more than 2035 Begonia species (Begoniaceae) reported currently in the world. Begonia arachnoidea was found as a new species within a small area in Southern China. In this study, we are reporting for the first time its chloroplast genome for the purpose to compare with the chloroplast genomic data from other plant taxa which were closely related to this new species. Our results show that the circular chloroplast genome of B. arachnoidea is 169,725 bp in length, with 35.49% GC content. The whole structure of the genome has 76,431 bp in a large single-copy (LSC) region, 18,146 bp in a small single-copy (SSC) region, and the two inverted repeat (IRs) regions are both 37,574 bp. There are 90 protein-coding genes, 8 rRNA genes, and 42 tRNA genes encoded in this genome. Final phylogenetic analysis revealed that B. arachnoidea is genetically closest to B. pulchrifolia and B. coptidifolia.